Glycated Hemoglobin as a Screening Tool in the Diagnosis of Diabetes Mellitus among Adult Patients in a Tertiary Health Facility in Port Harcourt, Niger Delta Region of Nigeria - Gesiye Bozimo; Marcellinus Okafor Nkpozi; Adaeze Ugwu; Victoria Eno Gomba; Chinweuba M. Abonyi; Chioma Unachukwu (APIK Journal of Internal Medicine)
Background: The prevalence of diabetes mellitus (DM) has been increasing worldwide, especially in Nigeria. However, it remains underdiagnosed in many people with the disease. There is a need for early detection and treatment of the populations that are at risk to prevent or reduce complications. There is a paucity of Nigerian studies documenting the performance of the glycated hemoglobin (HbA1c) test in diagnosing DM. This, therefore, informed our decision to embark on this study. Objective: The objective of this study was to assess the role of the HbA1c in the diagnosis of DM at the University of Port Harcourt Teaching Hospital. Materials and Methods: This was a descriptive cross-sectional study, in which 400 subjects were evaluated for the presence of glucose intolerance. Two hundred patients with hypertension and 200 nonhypertensives patients were screened for DM. A structured questionnaire was administered to the recruited subjects, and their blood samples were collected for HbA1c and fasting plasma glucose. The detection of DM using the two different screening tests was determined. The sensitivity and specificity were calculated. Results: The mean age of the hypertensive subjects was 48 ± 10 years, whereas that of the nonhypertensive subjects was 46 ± 10 years. The frequency of diabetes in the study population by the HbA1c was 7.8%, whereas it was 25.3% by the oral glucose tolerance test (OGTT) (P < 0.001). The frequency of prediabetes was 25.3% by the HbA1c as compared to 20.5% by the OGTT (P < 0.001). The sensitivity of the HbA1c test for the diagnosis of diabetes was 62.5%, whereas the specificity was 99.7%. Conclusions: This study shows that there was a significant difference in the diagnostic performance of the HbA1c test compared to the OGTT; HbA1c test was less accurate and more likely to miss some diagnoses.